CXCL12-CXCR4-Mediated Chemotaxis Supports Accumulation of Mucosal-Associated Invariant T Cells Into the Liver of Patients With PBC - Chen, Zhilei; Liu, Suying; He, Chengmei; Sun, Jinlei; Wang, Li; Chen, Hua; Zhang, Fengchun (Frontiers in Immunology, 2021)
Objectives: To explore the potential role of CD3+CD8+CD161high TCRVα7.2+ MAIT cells in the pathogenesis of primary biliary cholangitis (PBC). Methods: We enrolled 55 PBC patients, 69 healthy controls, and eight hepatic hemangioma patients. Circulating MAIT cells and their chemokine receptor profiles and cytokine production were quantified using ﬂow cytometry. Liver-resident MAIT cells were examined by immunofluorescence staining. CXCL12-mediated chemotaxis of MAIT cells was measured using transwell migration assay. Plasma IL-18 was measured using ELISA, and cytokine production in IL-18-stimulated MAIT cells was detected using ﬂow cytometry. Results: Peripheral MAIT cells were significantly decreased in PBC patients (3.0±3.2% vs. 9.4±8.0%, p<0.01) and were negatively correlated with alkaline phosphatase levels (r=-0.3209, p<0.05). Liver immunofluorescence staining suggested that MAIT cells might accumulate in PBC liver. MAIT cells from PBC patients expressed higher levels of CXCR4 (84.8±18.0% vs. 58.7±11.4%, p<0.01), and CXCL12 expression was higher in PBC liver. CXCL12 promoted MAIT cell chemotaxis (70.4±6.8% vs. 52.2±3.5%, p<0.01), which was attenuated by CXCR4 antagonist. MAIT cells from PBC produced significantly more IFN-γ (88.3±4.2% vs. 64.2±10.1%, p<0.01), TNF-α (93.0±1.1% vs. 80.1±5.3%, p<0.01), Granzyme B (89.3±3.3% vs. 72.1±7.0%, p<0.01), and perforin (46.8±6.6% vs. 34.8±7.7%, p<0.05). MAIT cells from PBC expressed higher levels of IL18-Rα (83.8±10.2% vs. 58.3±8.7%, p<0.01). Plasma IL-18 was more abundant in PBC patients (286.8±75.7 pg/mL vs. 132.9±78.1 pg/mL, p<0.01). IL-18 promoted IFN-γ production in MAIT cells (74.9±6.6% vs. 54.7±6.7%, p<0.01), which was partially attenuated by blocking IL-18R (68.6±8.3% vs. 43.5±4.2%, p<0.01). Conclusions: MAIT cells from PBC patients accumulated in liver via CXCL12-CXCR4-mediated chemotaxis, produced proinflammatory cytokines, and contributed to portal inflammation, which was potentially mediated by elevated IL-18. Targeting MAIT cells might be a therapeutic approach for PBC.